A Review of the Therapeutic Potential of Ginseng and Its Bioactive Components in Nonalcoholic Fatty Liver Disease - Hao L; Li S; Li C; Zhang Z; Hu X; Yan H (Drug Design, Development and Therapy)
Liyuan Hao,1,2,* Shenghao Li,1– 3,* Caige Li,4 Zhiqin Zhang,5 Xiaoyu Hu,2 Huimin Yan3 1School of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China; 2Department of Infectious Diseases, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China; 3Clinical Research Center, Shijiazhuang Fifth Hospital, Shijiazhuang, Hebei, People’s Republic of China; 4Department of Endocrinology, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 5College of Integrated Traditional Chinese and Western Medicine, Hebei University of Traditional Chinese Medicine, Shijiazhuang, Hebei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoyu Hu; Huimin Yan, Email xiaoyuhu202206@163.com; yanhm2538@163.comAbstract: Non-alcoholic fatty liver disease (NAFLD) is the major cause of chronic liver disease worldwide, with no universally recognized effective treatments currently available. In recent years, ginseng and its principal active components, such as ginsenosides, have shown potential protective effects in the treatment of these liver diseases. In NAFLD, studies have demonstrated that ginseng can improve hepatic lipid metabolism, reduce inflammatory responses, and inhibit oxidative stress and fibrosis, thereby attenuating the progression of NAFLD. Additionally, ginseng inhibits oxidative stress by scavenging free radicals and enhancing antioxidant enzyme activities, and it can impede fibrosis by interfering with the fibrotic signaling pathways. These combined effects contribute to attenuating the progression of NAFLD. These findings highlight the promise of ginseng as a potential therapeutic candidate for the treatment of NAFLD. However, despite the significant efficacy of ginseng in human NAFLD treatment, the number and quality of clinical studies remain limited, with a lack of large-scale, multicenter clinical trials to confirm these effects. Moreover, the pharmacokinetic properties of different ginsenosides, optimal therapeutic dosages, and the safety of long-term use require further investigation. This review summarizes the existing evidence on the mechanisms of action of ginseng and its active components in human NAFLD, assesses their potential as therapeutic options, and proposes future research directions to provide stronger scientific support for clinical application. Additionally, we performed a network pharmacology analysis of ginseng in relation to NAFLD to identify and investigate potential targets of ginseng in the treatment of NAFLD. This analysis aims to provide a theoretical foundation for the development of ginseng -based drugs for combating NAFLD.Keywords: ginseng, bioactive components, NAFLD, NASH